THE EFFECT OF RETAILING MIX ON COSMETIC PURCHASE DECISION (Case Study at Roma Cosmetic Store in Lhokseumawe City) - Dirra Vachira; Yuli Asbar; Naufal Bachri; Mariyudi (RADJA PUBLIKA, 2023)
This study aims to find out how the influence of retailing mix on cosmetic purchasing decisions at the Roma Cosmetik Store in Lhokseumawe City. The independent variables used in this study consisted of product, price, location, service, promotion, and store atmosphere. The data used in this study was primary data obtained by distributing questionnaires to 96 respondents who made cosmetic purchases at the Cosmetic Roma Store in Lhokseumawe City. The data analysis technique used is multiple linear regression analysis using the help of SPSS software version 26. The results showed that products, prices, services, and promotions partially had a positive and significant effect on the purchase decision of cosmetics at the Roma Cosmetik Store in Lhokseumawe City. Meanwhile, the location and atmosphere of the store have a positive but not significant effect on the decision to buy cosmetics at the Roma Cosmetik Store in Lhokseumawe City. Meanwhile, the results of simultaneous testing showed that the product, price, location, service, promotion, and store atmosphere simultaneously had a significant effect on the purchase decision of cosmetics at the Roma Cosmetik Store in Lhokseumawe City.